Tensile properties of composites with glass fibers and curauá fibers in polyester resin matrix - Queiroz, Syme Regina Souza; Alves, Felipe Augusto dos Santos; Freire, Giâcomo dos Santos; Queiroz, Nilton Cesar Almeida; Silva , Vera Lucia Dias da (Seven Editora, 2023)
Synthetic glass fiber is used by several industrial segments, including civil construction in northern Brazil, due to its characteristics and properties that allow lightness and durability to manufactured products. Curauá (Ananas erectifolius), is a plant with flat, hard leaves that occurs in the state of Pará, from which fiber is extracted that may represent great potential for use in composites for the civil construction industry. Thus, polymer composites with polyester resin matrix and reinforcement with short glass and curauá fibers, both 15 mm long and randomly distributed, were produced for comparison of tensile properties. The first results showed better mechanical performance in tensile of the composites reinforced with curauá fibers in relation to composites with glass fibers, on average 53,17%. The water absorption tests of the composites showed similar values, 1.75% with curauá fibers and 1.73% with glass fibers, indicating good wettability of both fibers. The micrographs of the fracture zones in the tensile tests showed better interfacial interaction of the composites with curauá fibers. DOI:https://doi.org/10.56238/uniknowindevolp-043